Risk, Return and Risk Aversion: A Behavioral Rendition - Ting, Hian Ann, Christopher (Institutional Knowledge at Singapore Management University, 2004)
Behavioral finance and classical finance based on utility maximization appear to be mutually exclusive schools of thought. Despite the fundamental difference, we show that behavioral finance also has a linear relation between risk and return. This relation is obtained without the assumptions of market equilibrium, rational expectations, a specific utility function and the market portfolio. In the behavioral approach, the pricing error of CAPM is not an error. It is attributable to the higher-order moments of return. Empirical tests suggest that the relative risk aversion coefficient is positive and time-varying. Moreover, it correlates negatively with both volatility and return.